PCSK9 is associated with mortality in patients with septic shock: data from the ALBIOS study. (30th July 2020) - Vecchié, A.; Bonaventura, A.; Meessen, J.; Novelli, D.; Minetti, S.; Elia, E.; Ferrara, D.; Ansaldo, A. M.; Scaravilli, V.; Villa, S.; Ferla, L.; Caironi, P.; et al.
Abstract: Background: Pro‐protein convertase subtilisin/kexin 9 (PCSK9) is a proenzyme primarily known to regulate low‐density lipoprotein receptor re‐uptake on hepatocytes. Whether PCSK9 can concurrently trigger inflammation or not remains unclear. Here, we investigated the potential association between circulating levels of PCSK9 and mortality in patients with severe sepsis or septic shock. Methods: Plasma PCSK9 levels at days 1, 2 and 7 were measured in 958 patients with severe sepsis or septic shock previously enrolled in the Albumin Italian Outcome Sepsis (ALBIOS) trial. Correlations between levels of PCSK9 and pentraxin 3 (PTX3), a biomarker of disease severity, were evaluated with ranked Spearman's coefficients. Cox proportional hazards models were used to assess the association of PCSK9 levels at day 1 with 28‐ and 90‐day mortality. Results: Median plasma PCSK9 levels were 278 [182–452] ng mL −1 on day 1. PCSK9 correlated positively with PTX3 at the three time‐points, and patients with septic shock within the first quartile of PCSK9 showed higher levels of PTX3. Similar mortality rates were observed in patients with severe sepsis across PCSK9 quartiles. Patients with septic shock with lower PCSK9 levels on day 1 (within the first quartile) showed the highest 28‐ and 90‐day mortality rate as compared to other quartiles. Conclusion: In our sub‐analysis of the ALBIOS trial, we found that patients with septic shock presenting with lower plasma PCSK9 levels experienced higher mortality rate. Further studies are warranted to better evaluate the pathophysiological role of PCSK9 in sepsis. Abstract :